Fine‐Scale Variability of Observed and Simulated Surface Albedo Over the Southern Great Plains. Issue 7 (9th April 2020) - Berg, Larry K.; Long, Charles N.; Kassianov, Evgueni I.; Chand, Duli; Tai, Sheng‐Lun; Yang, Zhao; Riihimaki, Laura D.; Biraud, Sébastien C.; Tagestad, Jerry; Matthews, Alyssa; Mendoza, Albert; Mei, Fan; et al.
Abstract: Surface albedo can be highly variable in both space and time. The Department of Energy's Holistic Interactions of Shallow Clouds, Aerosols, and Land‐Ecosystems field study provides a unique opportunity to characterize the variability of surface albedo over the Southern Great Plains of the United States using integrated tower, aircraft, and satellite observations. The primary advantage of the aircraft and satellite observations is the ability to examine the spatial distribution of surface albedo over a large area, while the tower measurements have the ability to examine both diurnal and day‐to‐day variability at a single location. In general, consistency was found between the broadband (BB) albedo measured from the surface, air, and space. There was a small increase from 0.186 to 0.194 in the aircraft BB surface albedo between May and September (about 4% change), while the Moderate Resolution Imaging Spectroradiometer black‐sky BB surface albedo increased from 0.151 to 0.166 over the same period (about 10% change), while the standard deviations in the aircraft and Moderate Resolution Imaging Spectroradiometer BB albedo were similar. The largest seasonal differences in the aircraft BB albedo were found for areas with winter wheat or forest, while areas with pasture or grasses showed a smaller seasonal diversity. The Weather Research and Forecasting model was used to simulate the BB surface albedo. In comparison with the aircraft and satellite observations, the Weather Research and Forecasting‐simulated BB surface albedo had no seasonal change and a much narrower distribution. Plain Language Summary: The sunlight reflected by the surface has a large impact on the amount of energy that is available to warm the surface or evaporate water either standing on the surface or trapped in the soil. There are three primary ways to measure the reflection: using tower, aircraft, or satellite. Each approach has advantages and disadvantages, including different fields of view, the wide range of land use under the aircraft and satellite flight tracks, and corrections to account for scattering and absorption of sunlight by clouds and particles in the atmosphere. In this study, we compare tower, aircraft, and satellite measurements made during the Holistic Interactions of Shallow Clouds, Aerosols, and Land‐Ecosystems field study. We find differences in the amount of energy that is reflected, which changes with season and we highlight that the differences can be related to land use. We compare observations to simulations completed using the Weather Research and Forecasting model. The modeled reflectance shows little seasonal change and tends to underestimate the variability of the reflectance. These results have significant impacts for other studies focused on the amount of sunlight that is absorbed at the surface and the impact on land‐atmosphere interactions. Key Points: Observed and simulated broadband surface albedo are presented Spatial variability of surface albedo is described Aircraft and satellite measurements of surface albedo are compared to results from the Weather Research and Forecasting model simulations